The Different Antibacterial Impact of Silver Nanoparticles Against Legionella pneumophila Compared to Other Microorganisms - M.R. Pourmand; K. Shahidi; P. Nazari; Seyed M. Moosavian; N. Samadi; Gh. Pourmand; A. R. Shahverdi (Journal of Sciences, Islamic Republic of Iran)
Legionella pneumophila is the pathogen responsible for severe pneumonia known as Legionnaires’ disease. Legionella can live under varied stress conditions, especially in cold environments, and is common in many artificial environments. In this study, the antimicrobial activity of biogenic silver nanoparticles, prepared using the culture supernatant of Klebsiella pneumoniae, was evaluated against different important microorganisms, especially L. pneumophila. Compared with all bacterial test strains, L. pneumophila showed lower susceptibility against silver nanoparticles (MIC 30 µg/mL). The MICs of silver nanoparticles were 10 µg/ml for Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia marcescens, and Salmonella typhi. In addition, the MIC values of the silver nanoparticles for the fungal teststrain(Aspergillus niger and Candida albicans) were 20 and 30 µg/ml, respectively. The time-kill course antibacterial assay of silver nanoparticles at its MIC concentration (30 µg/mL) was performed against L. pneumophila at cold (4 °C) and ambient (25 °C) temperatures. The results showed that a higher mortality rate was observed at 4 °C. In contrast, at 25 °C,a considerable tolerance was observed for L. pneumophila against 30 µg/ml of silver nanoparticles during the 24-h exposure time. Reserpine as a natural efflux inhibitor (10 µg/mL) was used in this study to reverse the resistance of L. pneumophila against silver nanoparticles at 25 °C. Higher anti-legionella activity was detected in the presence of reserpine at the mentioned temperature that indicated that efflux pumps may have an important role in the resistance of L. pneumophila against silver nanoparticles at 25 °C.